A novel proof of concept approach towards generating reference microplastic particles - Simon D.J. Oster; Paul E. Bräumer; Daniel Wagner; Max Rösch; Martina Fried; Vinay K.B. Narayana; Eva Hausinger; Helena Metko; Eva C. Vizsolyi; Matthias Schott; Christian Laforsch; Martin G.J. Löder (Microplastics and Nanoplastics)
Abstract For almost two decades now, scientists have increasingly focused on the occurrence of microplastic particles (MPs) in the environment and their impact on environmental and human health. Currently, the variety of analytical methods used in microplastic research result in data of different quality. This largely hampers comparability between data sets and consequently prevents a reliable risk assessment. In this context, the lack of suitable reference microplastic particles (RMPs) that can be added as an internal standard in an exactly known number further prevents quality assessment of, and harmonization in terms of comparability between different analytical methods. Although this challenge has been widely recognized, the availability of RMPs is currently limited to commercially available particles in the form of micro-beads or -fragments (powders). Manual addition of such RMPs to samples in a precisely defined number as an internal standard is inefficient and the alternative use of MP suspensions does not allow for the addition of an exactly defined particle number. The optimum solution to solve this issue would be RMPs embedded in an easy-to-use soluble matrix in exact numbers. This would allow for evaluating analytical quality during microplastic analysis as well as establishing harmonization in terms of comparability between different methods. In the present study we focused on the development of such RMPs. We used computerized numerical controlled (CNC) milling to produce small diameter plastic columns followed by gelatine embedment and subsequent cryosectioning. This results in gelatin slices containing an exactly defined number of RMPs with well-defined size, shape and polymer type / chemical composition that can be added to a sample easily with the dissolution of the gelatine. We successfully produced square shaped RMPs in a size range of 125–1000 μm of five different polymers. The overall size-deviation of the RMPs never exceeded ± 11.2% from the mean value of a set of particles. The highest percentage mass-deviation was 25.5% from the mean value of a set of 125 × 125 × 20 μm polystyrene (PS) RMPs. Our approach allows for the production of RMPs tailored to specific needs of all different analytical methods used in current microplastic research. Beyond analytical method validation, these RMPs furthermore open possibilities for experiments on MPs in different fields.